2020
DOI: 10.1037/cdp0000277
|View full text |Cite
|
Sign up to set email alerts
|

The association between maternal criticism and body dissatisfaction on disordered eating pathology across racial and ethnic groups.

Abstract: Objectives: Limited research exists examining the association of maternal weight-, shape-, and size-related criticism with disordered eating pathology across racial and ethnic groups. Method: The sample consisted of 392 undergraduate females and 368 undergraduate males for a total of 760 individuals. Disordered eating pathology, body dissatisfaction, and maternal criticism were assessed in 484 White, 134 Latinx, and 142 Asian American undergraduates. Hierarchical regression, correlation, and t-test analyses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 61 publications
2
14
0
Order By: Relevance
“…For example, the Children’s Eating Attitudes Test has been used in some studies on disordered eating among adolescents [ 77 , 87 ]. The Eating Disorder Examination Questionnaire is another commonly used tool to measure disordered eating in Western contexts [ 88 90 ]. Moreover, the Eating Disorders Inventory-2 has been applied to measure disordered eating in Western and Southeast Asian contexts [ 56 , 57 ].…”
Section: Limitationsmentioning
confidence: 99%
“…For example, the Children’s Eating Attitudes Test has been used in some studies on disordered eating among adolescents [ 77 , 87 ]. The Eating Disorder Examination Questionnaire is another commonly used tool to measure disordered eating in Western contexts [ 88 90 ]. Moreover, the Eating Disorders Inventory-2 has been applied to measure disordered eating in Western and Southeast Asian contexts [ 56 , 57 ].…”
Section: Limitationsmentioning
confidence: 99%
“…Although studies have demonstrated that self‐oriented perfectionism contributes to EDs across various populations (Bulik et al, ; Castro‐Fornieles et al, ; Shafran & Mansell, ), less is known about the effects of parent‐oriented perfectionism. However, parental expectations and criticism tend to be elevated in collectivist cultures that emphasize filial piety, respect, and obedience—all of which could negatively impact mental health outcomes, including EDs (Chang et al, ; DiBartolo & Rendon, ; Yu & Perez, ). This investigation specifically assessed relations among participants’ perceptions of PC and PE and body dissatisfaction, restraint, LOC eating, purging, and compensatory exercise in White, Black, Latina, Asian American, and multiracial college women.…”
Section: Discussionmentioning
confidence: 99%
“…High parental pressure, in particular, appears uniquely related to EDs, relative to other psychiatric conditions (Horesh et al, ). Additionally, young women experiencing parental criticism are more likely to report disordered eating, especially bulimic symptoms (de Leon‐Vasquez, Villalobos‐Hernandez, Rivera‐Marquez, & Unikel‐Santoncini, ; Hanna & Bond, ); however, these associations might vary by racial/ethnic group, potentially due to differing cultural values (e.g., individualism vs. collectivism) (Yu & Perez, ). Further investigation could elucidate relations between parent‐oriented perfectionism and disordered eating across cultural groups.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, to the extent that interdependent relationships come with a greater sense of obligation (Adams & Plaut, 2003), ensuring that all members feel accepted in terms of their physical selves may also help to ensure that social harmony is maintained. Indeed, there is some evidence that appearance commentary is both common and socially acceptable in interdependent cultures, although much of the available research has focused on negative elements (e.g., criticism of appearance, mixed messages about weight and eating; Smart & Tsong, 2014;Yu & Perez, 2020). In addition, interdependent selfconstrual is associated with greater perceived familial and global support (Goodwin & Plaza, 2000).…”
Section: Study 2: Invariance Across National Groupsmentioning
confidence: 99%